THE ACCEPTANCE OF AUDIT GOING CONCERN OPINION ON COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Fera Tjahjani; Widanarni Pudjiastuti (Adbis: Jurnal Administrasi dan Bisnis, 2017)
This studyinvestigates correlation between audit quality, financial performance, debt default, size of the firm, and audit tenure on going concern opinion acceptance. Samples used all companies which listed in Indonesia Stock Exchange beside manufacturing, banks and other financial institution during 2011-2013. Data collected by purposive sampling. The study provides empirical evidences that audit quality, financial performance had negative influences on audit going concern opinion acceptance, while leverage and audit tenure had positive ones. However, debt default and size of the entities had no relationship on it.